2018
DOI: 10.15244/pjoes/76677
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Contents in Yellow Lupine (Lupinus luteus L.) and Blue Lupine (Lupinus angustifolius L.) Cultivars Depending on Habitat Conditions

Abstract: Covering requirements for high-quality protein in animal feed and human food is becoming more and more important in EU countries, including Poland. Over the past 30 years, around 70% of plant protein requirements in Poland have been covered by imported extracted soybean meal. Population growth, changing weather conditions, and a decrease in arable lands have forced farmers to grow other species that provide feed and food and constitute plant proteins [1]. Legume seeds may play such a role. Lupines are a specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The lupine plant is considered adequate for sustainable agriculture due to its capacity to fix atmospheric nitrogen in the soil [3] and its suitability for crop rotation, being a good precursory for other plant cultures [4]. However, the nutrient content of lupine seeds and their quality are influenced by the species, cultivars, selected agrotechniques and pedoclimatic factors for plant growth [5]. New sweet lupine cultivars from low-alkaloid varieties (less 0.02%) do not require heat treatment of the seeds in order to eliminate thermolabile compounds, like in the case of soybeans, because of their low content of protease inhibitors, tannins, saponins, lectins.…”
Section: Introductionmentioning
confidence: 99%
“…The lupine plant is considered adequate for sustainable agriculture due to its capacity to fix atmospheric nitrogen in the soil [3] and its suitability for crop rotation, being a good precursory for other plant cultures [4]. However, the nutrient content of lupine seeds and their quality are influenced by the species, cultivars, selected agrotechniques and pedoclimatic factors for plant growth [5]. New sweet lupine cultivars from low-alkaloid varieties (less 0.02%) do not require heat treatment of the seeds in order to eliminate thermolabile compounds, like in the case of soybeans, because of their low content of protease inhibitors, tannins, saponins, lectins.…”
Section: Introductionmentioning
confidence: 99%
“…Księżak et al [35] in previous studies showed that regardless of the habitat conditions varieties of blue lupine (Graf and Tango) and yellow lupine (Dukat, Table 7.…”
Section: Resultsmentioning
confidence: 93%
“…Niwińska [38] reports that much less proteins contain sweet lupine seeds than alkaloid ones. Obtained results by Księżak et al [35] indicate that the evaluated varieties of yellow lupine were characterized by a similar fiber content; only the Perkoz variety contained significantly more of this component than Parys, whereas in the case of blue lupine, it contained the least Neptun variety and indeed more varieties Karo, Boruta, Graf, Bojar, and Kadryl. Niwińska [39] noted species and varietal diversity in fiber accumulation.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Jaiswal et al (2018) found that Al 3+ has lethal effects on many aspects of the rhizobia/legume symbiosis, which include a decrease in root elongation, root hair formation and suppression of nitrogen metabolism. Soil pH also influences the accumulation of proteins in the grain of pulse crops (Księżak et al 2018).…”
mentioning
confidence: 99%